PENCAHAYAAN YANG SEHAT DAN EFISIEN: INTEGRASI ASPEK UTILITAS BANGUNAN DAN KESEHATAN MATA DALAM DESAIN INTERIOR - Tara, Renata; Deca Pratama, Rian; Eka Prasetya, Rifqi; Agustian Nugroho, Risky; Cantika Putri, Rossa; Pratama, Ryan (Universitas Muhammadiyah Metro, 2025)
Lighting in interior design has a crucial role not only in creating space aesthetics, but also in supporting eye health and energy efficiency. This research explores the integration of utility and eye health aspects in optimal interior lighting design. A holistic design approach is required to create spaces that are visually comfortable, as well as energy efficient. The research reviewed various lighting types, arrangement techniques, and material selection that minimize the risk of eye disorders and maximize energy efficiency. The results of this research are expected to provide practical guidance for interior designers and architects in creating healthy, comfortable and sustainable spaces. This article discusses how the integration of utility and eye health aspects can result in optimal lighting for occupants. Proper implementation of natural and artificial lighting not only improves energy efficiency but also reduces the risk of eyestrain, visual stress and sleep disorders. By considering factors such as intensity, light distribution, and selection of lamp color and type, healthy lighting design can improve user productivity and well-being. Through a holistic approach, this research highlights the importance of synergy between aesthetics, function and health in the design of efficient and eye-friendly interior lighting.